Experimental and Numerical Study of Collector Geometry Effect on Solar Chimney Performance - Shyaa, Aseel K.; Albaldawi, Rafea A. H.; Abbood, Maryam Muayad (Al-Khwarizmi Engineering Journal, 2017)
There have been many advances in the solar chimney power plant since 1930 and the first pilot work was built in Spain (Manzanares) that produced 50 KW. The solar chimney power plant is considered of a clean power generation that needs to be investigated to enhance the performance by studying the effect of changing the area of passage of air to enhance the velocity towards the chimney to maximize design velocity. In this experimental and numerical study, the reduction area of solar collector was investigated. The reduction area that mean changing the height of glass cover from the absorbing plate (h1=3.8cm, h2=2.6cm and h3=1.28cm). The numerical study was performed using ANSYS Fluent software package (version 14.0) to solve governing equations. The aim of this work was to study the effect of change the height of reduction area to the design velocity (velocity move the blade of turbine at inlet in the chimney). The results showed that the third height (h3=1.28cm) gives the best result because when decreasing the height between the glass cover and absorbing plate, the area between them decreased and the design velocity increased then the efficiency of solar chimney model was increased.